Two Distinct Interferon-γ in the Orange-Spotted Grouper (Epinephelus coioides): Molecular Cloning, Functional Characterization, and Regulation in Toll-Like Receptor Pathway by Induction of miR-146a - Peng, Wan; Sun, Yan; Li, Gao-Fei; He, Liang-Ge; Li, Ruo-Zhu; Liang, Yao-Si; Ding, Xu; Yu, Xue; Zhang, Yong; Lin, Hao-Ran; Lu, Dan-Qi (Frontiers in Endocrinology, 2018)
Interferon gamma (IFNγ) is a Th1 cytokine that is critical for innate and adaptive immunity. Toll-like receptors (TLRs) signalling pathways are critical in early host defence against invading pathogens. miR-146a has been reported to participate in the regulation of host immunity. The known mechanisms of integrations between the IFNγ and TLR signalling pathways are incompletely understood, especially in teleosts. In this study, orange-spotted grouper (Epinephelus coioides) IFNγ1 and IFNγ2, their biological activities, especially their involvements in TLR pathway were explored. We identified and cloned two IFNγ genes of E. coioides, namely EcIFNγ1 and EcIFNγ2. The produced recombinant E. coioides IFNγ1 (rEcIFNγ1) and IFNγ2 (rEcIFNγ2) proteins showed functions which are similar to those of other bony fishes, such as enhancing nitric oxide responses and respiratory burst response. rEcIFNγ2 could regulate TLR pathway by enhancing the promoter activity of miR-146a upstream sequence and thus increasing the expression level of miR-146a, which possibly targets TRAF6, a key adapter molecule in TLR signaling pathway. Taken together, these findings unravel a novel regulatory mechanism of anti-inflammatory response by IFNγ2, which could mediate TLR pathway through IFNγ2-miR-146a-TRAF6 negative regulation loop. It is suggested that IFNγ2 may provide a promising therapeutic, which may help to fine-tune the immune response.